Hypertension prevalence and risk factors among residents of four slum communities: population-representative findings from Port-au-Prince, Haiti. Issue 4 (April 2019) - Tymejczyk, Olga; McNairy, Margaret L.; Petion, Jacky S.; Rivera, Vanessa R.; Dorélien, Audrey; Peck, Mireille; Seo, Grace; Walsh, Kathleen F.; Fitzgerald, Daniel W.; Peck, Robert N.; Joshi, Ashish; Pape, Jean W.; et al.
Abstract : Objectives: The aim of this study was to estimate the prevalence of hypertension and its risk factors among adults in four slum communities in Port-au-Prince. Methods: Cluster area random sampling was used to select adults for a health and demographic survey, including anthropometric measurements. Hypertension was defined as SBP at least 140 mmHg and/or DBP at least 90 mmHg, or current hypertension treatment, and was age-standardized to WHO world population. Correlates of hypertension were tested using sex-stratified logistic regression. Results: Overall, 20.3% of adults had hypertension (28.5% age-standardized), including 22.3% of men and 18.9% of women. Three percent of participants reported current hypertension treatment, and 49.5% of them had their hypertension controlled. Overweight/obesity (BMI ≥25) was the most common risk factor (20.6% among men, 48.5% among women), while smoking was less common (11.8 and 3.9%, respectively). Increasing age and hypertension prevalence in immediate surroundings were associated with greater odds of hypertension. Among men, having in-migrated in the 3 years prior (versus ≥3 years) was also associated with hypertension [adjusted odds ratio (aOR)=3.32, 95% confidence interval (95% CI): 1.79–6.17], as was overweight and obesity (aOR = 1.90, 95% CI: 1.09–3.33, and aOR = 5.73, 95% CI: 2.49–13.19, respectively) and nonreceipt of needed medical care in the preceding 6 months (aOR = 2.82, 95% CI: 1.35–5.88) among women. Conclusion: Hypertension prevalence was high across the age spectrum, in addition to substantial levels of overweight/obesity and unmet healthcare needs. It is important to better understand the possible effects of intraurban migration and environmental risk factors on hypertension and ensure that the benefits of increasingly cost-effective prevention and treatment programmes extend to slum residents. Abstract : Supplemental Digital Content is available in the text